Near poverty – definition, factors, predictions - Sączewska-Piotrowska, Anna (Sfera blisko ubóstwa – definicja, czynniki, prognozy, 2016)
The aim of the paper was to analyse near poverty in Poland. The first specific aim was to analyse the transitions into and out of near poverty in Poland using the Markov transition matrix. Three poverty states were considered: poverty, near poverty (an income of between 100 and 125 per cent of the poverty threshold is assumed in the paper) and above near poverty. The analysis was conducted for Poland based on the balanced panel from 2009 to 2015, the framework of the “Social Diagnosis” project. The second specific aim was to determine the factors that increase and decrease the odds of being in near poverty using bi-nomial logistic regression
Ekonometria = Econometrics, 2016, Nr 4 (54), s. 82-94
Keywords: near poverty; poverty transitions; the Markov chain model; Shorrocks' mobility index; logistic regression; sfera blisko ubóstwa; przejścia pomiędzy stanami ubóstwa; łańcuchy Markowa; indeks mobilności Shorrocka; regresja logistyczna